LLM based expert AI agent for mission operation management - Sobhana Mummaneni; Syama Sameera Gudipati; Satwik Panda (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska)
Mission operation management is the coordination and control of various activities related to the operation of a satellite. This critical function involves planning, monitoring, controlling, and coordinating all aspects of the mission, ensuring the spacecraft achieves its objectives. Current mission operation management faces limitations in terms of data transmission relying solely on ground control, manual analysis procedures, and not capitalizing on technology for optimizing routine mission operations. This research proposal aims to develop a Large Language Model (LLM) based Expert AI agent for performing mission operation management. The proposed LLM based AI assistant will perform tasks such as data analysis for pattern recognition, operational planning, and document summarization. The system is designed to operate offline, providing flexibility in deployment. Integrating AI with mission operation management can benefit mission controllers and engineers, scientists and researchers, space agencies and organizations. AI offers opportunities to reduce mission costs, improve success rates, and enhance the efficiency of space exploration programs.